Zmienność przestrzenna powierzchniowych osadów plażowych brzegu morskiego wyspy Wolin - Tylkowski, Jacek; Samołyk, Mariusz (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2011)
The conducted morpholithological studies of beach deposits make it possible to determine the current morphodynamics of the coast of the Wolin Island. By comparing the average value of grains composing sediments of individual zones of the beach it can be stated that the highest energy is represented by the following: beach below the water line and then beach at the water line, beach in its central part and beach at the foot of the cliff/dune. The standard deviation of sediments indicates the lowest energy diversification at the beach within its central part and at the foot of the cliff/dune, and the highest – in the zone below the water line. Further enrichment of sediments in thicker material and elimination of finer fraction occur on the beach below the water line indicating selective elution and redisposition of the material and predominance of speeds which do not allow for the precipitation of finer sediment. Saltation is the major transportation factor within the whole beach zone. Analyzing the dynamics of the sedimentary environment on the basis of the C/M diagram, it was found that the beach below the water line is mainly composed of deposits formed under the conditions of high dynamic activity which is favourable to precipitation. While the beach above the water line is constructed of material made in turbulent environment, mainly due to rolling and saltation.
Keywords: Baltic littoral zone; beach deposits; Wolin Island